2016-2017 Recession: Perspectives of Women’s Vulnerability to Cassava Consumption and Cultivation in Nigeria’s Sub-Urban Space - Ema, Eti-obong Simeon (International Journal of Geography and Geology, 2019)
Women are an important factor of livelihood in every household especially in the African traditional society. As recession stretches their resilience, the perception of women’s vulnerability to cassava consumption and cultivation was revealed in the purposively sampled Epiri Nsukara suburban space of Uyo. A sample size of 384 exposed 81% respondents earn below the minimum wage with a prevailing rising cost of cassava, 75% acknowledged that family income does not encourage savings nor investments as purchase of food Cassava being paramount. Out of the 91% women farmers 63% identified high cost of cassava as their motivation for farming. These women were exposed to limited access to scientifically improved species of the crop stems, fertilizers, disease outbreaks, pest damage, and limited farm space. A community based approach to this emergency response should be carried out where concern institutions and stakeholders provide improved cassava stems, fertilizers and other farm inputs through an easily accessible value chain. Also, subsidies should be granted these farmers to encourage their purchase of these improved species. An active community-agriculture extension agent relationship should be in place to bridge the knowledge gaps that exist for adopting modern models and methods of cassava cultivation to increase cassava yield at a limited possible time.